Relationship between transgender and patriarchy in Taiwanese queer fiction (1990-1999) - Ngew, Mei Hui (2016)
The lifting of martial law had induced social movement in nineties Taiwan; queer theory was introduced there under this background as well. Queer is an umbrella term for all sexual and gender minorities like transgender people and so on. The visibility of transgender people among queers is particularly low. Thus, this study aims to investigate the subjectivity of transgender people from Taiwanese queer fiction in nineties. The term of transgender has meanings of “to change” as in “transform”, “to cross” as in “transcontinental” and “to move beyond” as in “transcutaneous”. Hence, this research will use “transsexual”, “butch” and “androgyny” as examples, to examine how patriarchy oppressed transgender people, and how transgender people reacted in return. It resulted in as transgender people constructed their queer identity successfully and fought back against oppression by queer performativity.